ROLE OF THANATOMICROBIOME PROFILING IN ESTIMATING THE POSTMORTEM INTERVAL (PMI) OF THE CADAVERS: A REVIEW (Journal of Forensic Medicine & Toxicology, 2020)
The post-mortem interval or time since death holds great importance in forensic investigations. This window of time between the death and discovery helps narrow down suspects and events by providing a direction for investigation to follow. Precise estimation of PMI is a difficult task. But what if we ask the dead about it? With microbial presence being ten times more than that of human cells in our body, why not seek their help? Ample of data exists about the microbial communities present in a living body. But of late, thanatomicrobiome has come up as a potential microbial marker to fill the gaps pertaining to the time and location of death. The present review article aims to focus the importance of thanatomicrobiome for forensic PMI estimations, its precision accuracy, objectivity and feasibility in the field. Besides, we aim to understand microbial community profiling technique that can be used for isolating essential microbiome data from postmortem samples. Finally, a glimpse about the future track and potential improvements that are possible in the field. Although various studies have identified the role of bacterial communities in PMI estimations, there remain some obstacles for their practical forensic use.
Keywords: Forensic thanatology; microbiome; PMI estimations; accuracy and reliability; medicolegal death investigations